Chronic kidney disease and the aging population - Marcello Tonelli; Miguel Riella (Pediatria i Medycyna Rodzinna, 2013)
The proportion of older people in the general pop‑ ulation is steadily increasing worldwide, with the most rapid growth in low- and middle-income countries(1). This demographic change is to be celebrat‑ ed, because it is the consequence of socioeconomic de‑ velopment and better life expectancy. However, popula‑ tion aging also has important implications for society – in diverse areas including health systems, labor mar‑ kets, public policy, social programs, and family dynam‑ ics(2). A successful response to the aging population will require capitalizing on the opportunities that this tran‑ sition offers, as well as effectively addressing its chal‑ lenges.